2015
DOI: 10.1111/cbdd.12602
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiproliferative Activity of Silybin Conjugates with Salinomycin and Monensin

Abstract: Aiming at development of multitarget drugs for the anticancer treatment, new silybin (SIL) conjugates with salinomycin (SAL) and monensin (MON) were synthesized, in mild esterification conditions, and their antiproliferative activity was studied. The conjugates obtained exhibit anticancer activity against HepG2, LoVo and LoVo/DX cancer cell lines. Moreover, MON-SIL conjugate exhibits higher anticancer potential and better selectivity than the corresponding SAL-SIL conjugate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 45 publications
2
20
0
4
Order By: Relevance
“…The double-modified MON derivatives have been synthesized by the reaction of MON with triphosgene as an activating reagent and the respective alcohol or amine leading to obtain ten double-modified ester-carbonate derivatives (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) and five double-modified amide-carbonate derivatives (12)(13)(14)(15)(16) with yields from 14% up to 82%, respectively (Supporting information Table S1). …”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The double-modified MON derivatives have been synthesized by the reaction of MON with triphosgene as an activating reagent and the respective alcohol or amine leading to obtain ten double-modified ester-carbonate derivatives (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) and five double-modified amide-carbonate derivatives (12)(13)(14)(15)(16) with yields from 14% up to 82%, respectively (Supporting information Table S1). …”
Section: Chemistrymentioning
confidence: 99%
“…MON inhibits the growth of colon cancer, lymphoma, and myeloma cells by inducing cell cycle arrest and apoptosis. [14,16,17] For these reasons, we decided to synthesize a new series of double-modified MON derivatives to evaluate how such modifications will affect their biological activity and cation complexation capacity. [3,[6][7][8][9][10][11] In 2009, Kallioniemi and coworkers applied high-throughput screening to test a set of drugs and drug-like molecules for their efficacy against a panel of prostate cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…6 What is important, the compounds obtained show very interesting biological activity, including high anticancer activity and selectivity. 6 Furthermore, different SAL bioconjugates with floxuridine, 7 Cinchona alkaloids 8 and silybin 9 have been synthesized. Results of the anticancer activity tests of these bioconjugates, especially floxuridine bioconjugates, have clearly shown that this type connection of SAL with other biologically active substances leads to the formation of interesting compounds, which may be used in the nearest future in the fight against cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Results of the anticancer activity tests of these bioconjugates, especially floxuridine bioconjugates, have clearly shown that this type connection of SAL with other biologically active substances leads to the formation of interesting compounds, which may be used in the nearest future in the fight against cancer. [7][8][9] However, to the best of our knowledge, no attempts have been made to synthesize SAL bioconjugates with amino acid esters. The synthesis of the compounds of this type is very interesting, because it is well known that the use of amino acid prodrugs and their derivatives improves poor solubility, poor permeability, sustained release, intravenous delivery, drug targeting as well as metabolic stability of the parent substances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation